2022
DOI: 10.1155/2022/6850342
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pomegranate Juice and Sumac Consumption in the Treatment of Outpatients with COVID-19

Abstract: Introduction. COVID-19, an epidemic of coronavirus infection, has become a major global threat. The coronavirus mainly targets the human respiratory system, followed by cytokine storm, and altered immune responses associated with disease progression and adverse outcomes. Sumac and pomegranate juice are rich in bioactive compounds, which potentially have antiviral activities. This study is aimed at investigating the effect of a diet based on the use of sumac and pomegranate juice on the treatment of outpatients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…One study used Viola odorata L. aqueous extract (violet syrup) [36]; one study used pomegranate juice added to SUMAC (a composition of tannins, flavonoids, anthocyanins, isoflavones, terpenoids, and diterpenes) [37]; one study used Covexir (Ferula foetida oleogum) [38]; one study used Zufa syrup (a composition of Nepeta bracteata, Ziziphus jujube, Glycyrrhizaglabra, Ficuscarica, Cordia myxa, Papaver somniferum, Fennel, Adiantumcapillus veneris, Viola, Viper's-buglosses, Lavender, and Iris) [39]; one study used sachets of Matricaria chamomilla L., Zataria multiflora Boiss., Glycyrrhiza glabra L., Ziziphus jujuba Mill., Ficus carica L., Urtica dioica L., Althaea officinalis L., Nepeta bracteata Benth, and capsules of Rheum palmatum L. rizhome, Glycyrrhiza glabra root, Punica granatum L. fruit peel, Rheum palmatum, and Nigella sativa L. [40]; one study used giloy, swasari ras, ashwagandha, and tulsi ghanvati [41]; one used a multicomponent over-the-counter formulation [42]; one used lacto-wolfberry [43]; one used aged garlic extract powder [44]; one used ephedra herb, apricot kernel, cinnamon bark and glycyrrhiza root [45]; one used ginseng [46]; two used broccoli sprout decoction [47,48]; one used a Chima qingwen decoction [49]; one used elderberry extract orally [50]; and one use posaconazole [51]. The administered doses ranged from 300 mg to 200 g per day, and the intervention period ranged from 4 days to 20 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…One study used Viola odorata L. aqueous extract (violet syrup) [36]; one study used pomegranate juice added to SUMAC (a composition of tannins, flavonoids, anthocyanins, isoflavones, terpenoids, and diterpenes) [37]; one study used Covexir (Ferula foetida oleogum) [38]; one study used Zufa syrup (a composition of Nepeta bracteata, Ziziphus jujube, Glycyrrhizaglabra, Ficuscarica, Cordia myxa, Papaver somniferum, Fennel, Adiantumcapillus veneris, Viola, Viper's-buglosses, Lavender, and Iris) [39]; one study used sachets of Matricaria chamomilla L., Zataria multiflora Boiss., Glycyrrhiza glabra L., Ziziphus jujuba Mill., Ficus carica L., Urtica dioica L., Althaea officinalis L., Nepeta bracteata Benth, and capsules of Rheum palmatum L. rizhome, Glycyrrhiza glabra root, Punica granatum L. fruit peel, Rheum palmatum, and Nigella sativa L. [40]; one study used giloy, swasari ras, ashwagandha, and tulsi ghanvati [41]; one used a multicomponent over-the-counter formulation [42]; one used lacto-wolfberry [43]; one used aged garlic extract powder [44]; one used ephedra herb, apricot kernel, cinnamon bark and glycyrrhiza root [45]; one used ginseng [46]; two used broccoli sprout decoction [47,48]; one used a Chima qingwen decoction [49]; one used elderberry extract orally [50]; and one use posaconazole [51]. The administered doses ranged from 300 mg to 200 g per day, and the intervention period ranged from 4 days to 20 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…One study used Viola odorata L. aqueous extract (violet syrup) [36]; one study used pomegranate juice added to SUMAC (a composition of tannins, flavonoids, anthocyanins, isoflavones, terpenoids, and diterpenes) [37]; one study used Covexir (Ferula foetida oleogum) [38]; one study used Zufa syrup (a composition of Nepeta bracteata, Ziziphus jujube, Glycyrrhizaglabra, Ficuscarica, Cordia myxa, Papaver somniferum, Fennel, Adiantumcapillus veneris, Viola, Viper's-buglosses, Lavender, and Iris) [39]; one study used sachets of Matricaria chamomilla L., Zataria multiflora Boiss., Glycyrrhiza glabra L., Ziziphus jujuba Mill., Ficus carica L., Urtica dioica L., Althaea officinalis L., Nepeta bracteata Benth, and capsules of Rheum palmatum L. rizhome, Glycyrrhiza glabra root, Punica granatum L. fruit peel, Rheum palmatum, and Nigella sativa L. [40]; one study used giloy, swasari ras, ashwagandha, and tulsi ghanvati [41]; one used a multicomponent over-the-counter formulation [42]; one used lacto-wolfberry [43]; one used aged garlic extract powder [44]; one used ephedra herb, apricot kernel, cinnamon bark and glycyrrhiza root [45]; one used ginseng [46]; two used broccoli sprout decoction [47,48]; one used a Chima qingwen decoction [49]; one used elderberry extract orally [50]; and one use posaconazole [51]. The administered doses ranged from 300 mg to 200 g per day, and the intervention period ranged from 4 days to 20 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…A review by Gao et al (2022) reported that topical herbal therapies demonstrated positive effects in the treatment of OD. Additionally, a study by Forouzanfar et al (2022) revealed that diets containing pomegranate juice and lacquer sap were effective in reducing symptoms such as olfactory and gustatory dysfunction in patients with neoconjunctivitis.…”
Section: Interventions Of Odmentioning
confidence: 99%